Antimicrobial Activity against Paenibacillus larvae and Functional Properties of Lactiplantibacillus plantarum Strains: Potential Benefits for Honeybee Health - Massimo Iorizzo; Bruno Testa; Silvia Jane Lombardi; Sonia Ganassi; Mario Ianiro; Francesco Letizia; Mariantonietta Succi; Patrizio Tremonte; Franca Vergalito; Autilia Cozzolino; Elena Sorrentino; Raffaele Coppola; et al. (MDPI AG, 2020)
Paenibacillus larvae is the causative agent of American foulbrood (AFB), a severe bacterial disease that affects larvae of honeybees. The present study evaluated, in vitro, antimicrobial activity of sixty-one Lactiplantibacillus plantarum strains, against P. larvae ATCC 9545. Five strains (P8, P25, P86, P95 and P100) that showed the greatest antagonism against P. larvae ATCC 9545 were selected for further physiological and biochemical characterizations. In particular, the hydrophobicity, auto-aggregation, exopolysaccharides production, osmotic tolerance, enzymatic activity and carbohydrate assimilation patterns were evaluated. The five L. plantarum selected strains showed suitable physical and biochemical properties for their use as probiotics in the honeybee diet. The selection and availability of new selected bacteria with good functional characteristics and with antagonistic activity against P. larvae opens up interesting perspectives for new biocontrol strategies of diseases such as AFB.